HLA Class I and II Diversity Contributes to the Etiologic Heterogeneity of Non-Hodgkin Lymphoma Subtypes - Wang, Sophia S; Carrington, Mary; Berndt, Sonja I; Slager, Susan L; Bracci, Paige M; Voutsinas, Jenna; Cerhan, James R; Smedby, Karin E; Hjalgrim, Henrik; Vijai, Joseph; Morton, Lindsay M; Vermeulen, Roel; et al. (Cancer research, 2018)
A growing number of loci within the human leukocyte antigen (HLA) region have been implicated in non-Hodgkin lymphoma (NHL) etiology. Here, we test a complementary hypothesis of "heterozygote advantage" regarding the role of HLA and NHL, whereby HLA diversity is beneficial and homozygous HLA loci are associated with increased disease risk. HLA alleles at class I and II loci were imputed from genome-wide association studies (GWAS) using SNP2HLA for 3,617 diffuse large B-cell lymphomas (DLBCL), 2,686 follicular lymphomas (FL), 2,878 chronic lymphocytic leukemia/small lymphocytic lymphomas (CLL/SLL), 741 marginal zone lymphomas (MZL), and 8,753 controls of European descent. Both DLBCL and MZL risk were elevated with homozygosity at class I HLA-B and -C loci (OR DLBCL = 1.31, 95% CI = 1.06-1.60; OR MZL = 1.45, 95% CI = 1.12-1.89) and class II HLA-DRB1 locus (OR DLBCL = 2.10, 95% CI = 1.24-3.55; OR MZL = 2.10, 95% CI = 0.99-4.45). Increased FL risk was observed with the overall increase in number of homozygous HLA class II loci (P trend < 0.0001, FDR = 0.0005). These results support a role for HLA zygosity in NHL etiology and suggests that distinct immune pathways may underly the etiology of the different NHL subtypes.Significance: HLA gene diversity reduces risk for non-Hodgkin lymphoma. Cancer Res; 78(14); 4086-96. ©2018 AACR.
Keywords: Heterozygote; lidé; Case-Control Studies; prospektivní studie; Female; Genetic Heterogeneity; celogenomová asociační studie; nehodgkinský lymfom; Humans; Histocompatibility Antigens Class I; studie případů a kontrol; heterozygot; Prospective Studies; Histocompatibility Antigens Class II; MHC antigeny I. třídy; mužské pohlaví; MHC antigeny II. třídy; ženské pohlaví; Lymphoma, Non-Hodgkin; Male; Genome-Wide Association Study; genetická heterogenita